ANALYSIS OF FINANCIAL DISTRESS IN TRANSPORTATION COMPANIES WITH THE ALTMAN Z-SCORE APPROACH - Agus Irawan; Adi Prasetyo; Dwi Irawan (Review of Applied Accounting Research (RAAR), 2021)
This study aims to analyze the potential for bankruptcy of companies in the public transportation sub-sector listed on the Indonesia Stock Exchange using the Altman Z-score model approach. The population of this study are transportation companies listed on the Indonesia Stock Exchange for the 2017-2019 period, the sample is only taken from the 3 largest transportation companies operating on land, sea and air. The results of calculations using the Altman Zscore method show that there is one company that is prone to bankruptcy. A business that is expected to go bankrupt in the year under review does not mean it will go bankrupt, it is just a warning to the business about the state of the business so that it can anticipate the most likely losses.